An unusual cause of obstructing laryngeal edema: Forestier’s disease. Case report and literature review - Tropiano, Paolo; De Bonis, Teodosio; Petruzzi, Gerardo; Zambonini, Giulia; Giommetti, Sauro; Faralli, Mario; Ricci, Giampietro (Acta Biomedica Atenei Parmensis, 2022)
Forestier’s Disease or Diffuse Idiopathic Skeletal Hyperostosis (DISH) is a systemic condition characterized by the ossification and calcification of ligaments and entheses. DISH is observed on all continents and in all races, but most commonly in men over 50 years of age. Clinical symptoms resulting from DISH are related to altered skeletal biomechanism that may lead to decrease range of motion and painful stiffness of the axial and peripheral locomotor apparatus. When hyperostosis is localized at the spine at the level of glottic plane, it can lean to ENT symptoms including swallowing disorders, dysphonia, rarely dyspnea. The case report proposed refers to a rare DISH clinical presentation with chronic dyspnea. Fiber optic laryngoscopy was performed: a mucous flap of the posterior wall of the sovraglottic larynx reduced the respiratory space, the edematous tissue was aspired below during inspiration. CT with contrast medium was performed and osteophitic process of the anterior longitudinal ligament was diagnosed, in complete absence of neoplastic neoformation. At first conservative treatment was decided and corticosteroid therapy was introduced. He was managed successfully with an anterior cervical osteophytectomy. DISH is not a rare disease, but it is often undiagnosed. This diagnostic hypothesis should be considered in elderly patients presenting with dysphagia, dysphonia, sleep apnea, pharyngeal globus, which are common symptoms in otolaryngology practice. The suspicion must lead to an endoscopic and radiologic investigations. Early diagnosis is important for the initiation of a multidisciplinary approach that will improve the patient’s quality of life.